Non-invasive diagnostics of pathogenic bacteria using a breath sampler in children with cystic fibrosis. (1st October 2022) - van Aerde, Koen J; Leegstraten, Aniek; van den Kieboom, Corné H; Merkus, Peter; Sintnicolaas, Coosje; Simons, Sami O; van der Flier, Michiel; de Groot, Ronald; de Jonge, Marien I
Abstract: Cystic fibrosis (CF) is a common autosomal recessive disease causing thick, viscous secretions leading to pulmonary infections with pathogenic bacteria. As part of routine patient care, colonization and infection with these bacteria is monitored with cough swab or sputum cultures and sometimes bronchoalveolar lavage. In this cross-sectional proof-of-concept study in a cohort of CF patients we collected swabs or sputa and exhaled breath samples with the modular breath sampler (MBS), a newly developed two-way non-rebreathing sampling device. Pathogen specific polymerase chain reactions (PCRs) were performed on the MBS samples and compared with the results obtained with conventional diagnostics (i.e. culturing of swabs and sputa). A control group of stable asthma patients was used as negative control for the MBS measurements. The pathogens detected using MBS and conventional culturing differed: S. aureus was found more often in swab or sputum samples whereas Pseudomonas aeruginosa and S. pneumoniae were found more often in MBS samples. We hypothesize that this is due to sampling of different compartments, MBS samples are derived from the lower respiratory tract while cultures from cough swabs and sputa are dominated by pathogens residing in the upper respiratory tract. Another important difference is the readout, i.e. culture versus PCR. The majority of CF patients in whom P. aeruginosa was found did not have recent positive cultures suggesting higher sensitivity of MBS-based than conventional diagnostics. The majority of parents/patients found the MBS easy to use and less of a burden than respiratory sampling.